Social networks and the situation of blood donation in Poland: a logistics perspective = Sieci społeczne a sytuacja krwiodawstwa w Polsce w perspektywie logistycznej - Szołtysek, Jacek; Twaróg, Sebastian; Wronka-Pośpiech, Martyna (Zielona Góra: Faculty of Economics and Management Press)
This article aims to present the impact of social networks on the formation on the flow of blood and its components in the civilian blood donation system in Poland. The civilian blood donation system in Poland consists of 21 independently-functioning supply chains of blood and its components (Szołtysek, Twaróg 2009, p. 15). Today, logistics plays a secondary role in the management of blood supply chains, and the integration of flow is performed randomly and intuitively. The rapidly growing recognition of social logistics (T. Takahasi 1988, pp. 245 ? 251; Tenhunen 2008, pp. 515?534; Szołtysek 2010, pp. 2?6; Szołtysek 2011, pp.13?18) provides tools to improve the efficiency of the blood donation system in terms of both the existing blood supply chains, and the potential offered by network structures.
Keywords: logistyka społeczna; krwiodawstwo; sieci społeczne; social logistics; blood donation; social networks